Kihajar Dewantara's Views on Character Education and Its Relevance in the Learning of Faith and Morals in Elementary Madrasahs - Jarwo, Sujarwo; Muhamad Akip; Reni Marlina; Widia Putri (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
The view of character education is indeed the main focus in building a quality generation. This study seems very relevant in the context of education in Indonesia, especially in the Madrasah Ibtidaiyah (MI) environment which has an important role in shaping children's character from an early age. The concept of character education according to Ki Hadjar Dewantara, as you explained, emphasizes the instillation of moral values ​​and noble character. The "Among System" used in its implementation shows the importance of the role of interaction between teachers and students, and in the context of learning Akidah Akhlak, this is certainly very relevant. In learning Akidah Akhlak in MI, the moral and character concepts taught can be sourced from Islamic teachings and universal values ​​taught by Ki Hadjar Dewantara. Thus, this learning does not only cover academic aspects, but also the morals and character of students. The relevance of the concept of character education according to Ki Hadjar Dewantara for learning Akidah Akhlak in MI can be seen from the efforts to shape the character of students so that they become good and responsible human beings, and have respect for others and the surrounding environment. Thus, this research provides a significant contribution in efforts to improve the quality of character education in MI and strengthen moral values ​​in Islamic religious learning.